A comparative study on the energy absorption mechanism of aluminum/CFRP hybrid beams under quasi-static and dynamic bending. (June 2021) - Huang, Zhixin; Li, Ying; Zhang, Xiong; Chen, Wei; Fang, Daining
Abstract: The collapse of metal/composite hybrid beams under different load conditions is a critical mechanism for kinetic energy dissipation. However, the effects of load factors on bending collapse receive very few concerns, and their influences in energy absorption performance are still not clear. This work aims to conduct a comparative investigation on the quasi-static and dynamic bending collapse characteristics and energy dissipation mechanisms of aluminum/CFRP (Al/CFRP) hybrid beams. The deformation mechanisms of the Al/CFRP beams are studied by three-point bending tests and finite element analyses. The validated numerical method is then applied to explore the effect of CFRP layouts and load factors on the energy absorption performances. It is found that two deformation modes may be generated for the hybrid beam by varying the CFRP configuration, impact position, load velocity and impactor shape. The hybrid beam is more likely to collapse with a significant local indentation and achieves higher energy absorption efficiency under the conditions of non-middle impact positions, high velocities, and the relatively flat punch. With the variation of CFRP wrapping angles and load conditions, the specific energy absorption can be improved by 70.6% in the present analyses. The findings of this work will facilitate the crashworthiness design of Al/CFRP hybrid beams under transverse bending. Highlights: Quasi-static and dynamic bending tests are conducted for the Al/CFRP hybrid beams. Numerical method is adopted to simulate the test, and good agreements are achieved. The effect of load factors and CFRP layout on bending response are explored. The deformation mechanism, crushing force response and energy absorption performance under different load conditions are compared. The range of the specific energy absorption with the variation of load factors are concluded.